Analysis of The Effect of Side Friction on Urban Road Performance (Jl. Landorundun, Rantepao, Toraja) - Meilani Palimbong (Universitas Kristen Indonesia Paulus, 2025)
Jalan Landorundun is one of the main roads located in the bustling economic center of Rantepao city. Along this road there are shops, restaurants and market activities. This situation illustrates that the slowdown that occurs when vehicles pass along the road is caused by high roadside obstacles and disorderly traffic behavior from vehicles crossing the research location of this final project is on Jl. Landorundun, Rantepao District, North Toraja Regency, South Sulawesi. Primary data was obtained by conducting a direct survey in the field/research location, namely, Road Geometric, traffic volume, and side frition and secondary data, namely layout and population. This study used the Indonesian Road Capacity Guidelines (PKJI) 2014 analysis method, based on the results of the survey that has been conducted, the decrease in vehicle’ speed on Jl. Landorundun was caused by high side friction. The higher the side friction, the higher the degree of saturation. The higher the degree of saturation, the lower the road performance. The highest side friction occurred on Tuesday with a very high friction (ST) category of 1189.4 incidents/hour, due to market activities that occurred on that road section.